Construction of a nursing care protocol for children in post-hematopoietic stem cell transplantation - Jéssica Alline Pereira Rodrigues; Maria Ribeiro Lacerda; Cristina Maria Galvão; Ingrid Meireles Gomes; Marcia Regina Cubas; Ana Paula Pereira Fernandes (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective: To construct a nursing care protocol for children in post-hematopoietic stem cell transplantation. Method: Methodological research carried out from January to September 2019, in three steps: (a) integrative review (nursing care was identified); (b) theoretical structuring and organization of healthcare based on the Theory of Basic Human Needs and on the International Classification for Nursing Practice (supplementing the review data); and (c) development of a protocol in the three previously mentioned stages. Analysis of the understanding of the protocol's items/care was performed by three specialist nurses. Results: The care protocol consists of 40 nursing problems and is organized in accordance with the psychobiological, psychosocial, and psycho-spiritual needs of children undergoing transplantation, integrating practical and guidance care. Conclusion: The care protocol is an important technology for nursing care to transplanted children, aimed to prevent and manage transplantation complications.